2019
DOI: 10.3390/rs11182126
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of a Small Landslide in the Qinghai-Tibet Plateau by InSAR and Absolute Deformation Model

Abstract: Landslides are one of the major geohazards in the Qinghai-Tibet Plateau, and have recently increased in both frequency and size. SAR interferometry (InSAR) has been widely applied in landslide research, but studies on monitoring small-scale landslides are rare. In this study, we investigated the performance of Small Baseline Subsets method (SBAS) in monitoring small-scale landslide and further developed a new deformation model to obtain the absolute deformation time series. The results showed that SBAS could w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 71 publications
0
15
0
Order By: Relevance
“…Based on the annual deformation rate after conduction of hot spot analysis, 517 landslides with evident deformation and certain threats to railways were interpreted (Figure 8). Many detected landslides have been validated by field investigation and published articles, such as those pertaining to the Yigong landslide, Lancang River, Jinsha River, and Yalong River landslide groups [11,12,[38][39][40][41][42]. By comparing the identification results of hot spot analysis and traditional manual visual interpretation, it was found that traditional visual interpretation resulted in the exclusion of data on 178 missed landslides and 58 misjudged landslides.…”
Section: Active Landslide Inventorymentioning
confidence: 99%
“…Based on the annual deformation rate after conduction of hot spot analysis, 517 landslides with evident deformation and certain threats to railways were interpreted (Figure 8). Many detected landslides have been validated by field investigation and published articles, such as those pertaining to the Yigong landslide, Lancang River, Jinsha River, and Yalong River landslide groups [11,12,[38][39][40][41][42]. By comparing the identification results of hot spot analysis and traditional manual visual interpretation, it was found that traditional visual interpretation resulted in the exclusion of data on 178 missed landslides and 58 misjudged landslides.…”
Section: Active Landslide Inventorymentioning
confidence: 99%
“…The size and the resolution of detected damage depend on the spatial resolution of satellite data: from several meters to several tens of meters. Moreover, interferometric synthetic aperture radar (InSAR) enables us to estimate the amount of displacement within a few centimeters (e.g., [39][40][41]). Using these approaches, mass movement can be detected as pixel-by-pixel changes.…”
Section: Discussionmentioning
confidence: 99%
“…where λ is the wavelength, B ⊥ denotes the perpendicular baseline, θ and R denote the incidence angle and slant range distance, respectively, and t represents the time interval between two SAR scenes. In recent studies, The seasonal subsidence with a short time interval was successfully monitored based on the PSI (StaMPS-InSAR) [60] or DInSAR [61] method using Sentinel-1 data. The linear model with a short time interval used in seasonal subsidence monitoring is acceptable.…”
Section: Nsbas Methodsmentioning
confidence: 99%